The Leningrad Trials of German War Criminals in 1945–1946: Political Functions and Mediatization - Dmitrii Y. Astashkin (Historia provinciae: журнал региональной истории, 2020)
The article focuses on the Leningrad trials of Nazi war criminals (December 27, 1945 – January 6, 1946). Based on a wide range of sources, some of which are being introduced into scientific circulation for the first time, the political functions of the Leningrad trials are identified, and forms of their mediatization are determined. The Leningrad trials were supposed not only to sentence 11 specific criminals but also to condemn the occupation system in the region (the North-West of RSFSR) per se. The punitive actions of 1943–44 were most thoroughly investigated. However, the investigation could not or did not have enough time to identify those guilty of the Siege of Leningrad and the perpetrators of war crimes of 1941–42, including the Holocaust. The war crimes of Finnish and Spanish units in the territory of Leningrad Oblast and the participation of collaborators in those crimes were not investigated. Instead of these important issues, during the Leningrad trials the authorities chose to present false testimony of Private A. Düre about the Nazis’ guilt of the Katyn massacre (the testimony had neither political nor juridical effect). The Leningrad trials did not fully fulfil their political functions and escaped the culture of memory (among other reasons, due to selective mediatisation).